In the Right Place, at the Right Time: Spatiotemporal Conditions Determining Plasma Cell Survival and Function - Lindquist, Randall L.; Niesner, Raluca A.; Hauser, Anja E. (Frontiers in Immunology, 2019)
Plasma cells (PCs), the B lineage cells responsible for producing and secreting antibodies (Abs), are critical cellular components of the humoral immune system. While most of the antibody-secreting cells in the body have a rather short lifetime of a few days, some of them can become long-lived and persist in the body over the entire life span of an individual. The majority of these long-lived plasma cells secretes protective antibodies against pathogens, and are thereby crucial for the humoral component of immunological memory. The generation of these protective antibody-secreting cells can be triggered by an exposure to pathogens, and also by vaccination. Although the majority of plasma cells are protective, sometimes long-lived plasma cells produce autoreactive antibodies, which contribute to the pathogenesis and perpetuation of chronic autoimmune diseases, including lupus erythematosus, rheumatoid arthritis or multiple sclerosis. In order to promote the formation of protective antibody-secreting cells and to target pathogenic plasma cells, it is crucial to understand the signals which promote their longevity and allow them to exert their function. In recent years, it has become clear that plasma cells depend on extrinsic factors for their survival, leading to the concept that certain tissue microenvironments promote plasma cell retention and longevity. However, these niches are not static structures, but also have dynamic features with respect to their cellular composition. Here, we review what is known about the molecular and cellular composition of the niches, and discuss the impact of dynamic changes within these microenvironments on plasma cell function. As plasma cell metabolism is tightly linked to their function, we present new tools, which will allow us to analyze metabolic parameters in the plasma cell niches in vivo over time.